2022
DOI: 10.1029/2022ea002382
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Satellite Precipitation Data Sets for High Variability and Rapid Evolution of Typhoon Precipitation Events in the Philippines

Abstract: Extreme weather events, such as typhoons, have occurred more frequently in the last few decades in the Philippines. The heavy precipitation caused by typhoons is difficult to measure with traditional instruments, such as rain gauges and ground‐based radar because these instruments have an uneven distribution in remote areas. Satellite precipitation data sets (SPDs) provide integrated spatial coverage of rainfall measurements, even for remote areas. However, the speed and direction of the wind has the interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 107 publications
1
8
0
Order By: Relevance
“…Similar results for FAR, MAR, POD, and BIAS can be found in Supporting Information (Figure S7). BIAS shows that CMFD overestimates at light intensity while underestimates at high intensity, which is consistent with previous studies (Aryastana et al., 2022; Tang et al., 2021; Tian et al., 2018). And the detection capability of calibrated‐CMFD is also improved especially for the large precipitation magnitude.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results for FAR, MAR, POD, and BIAS can be found in Supporting Information (Figure S7). BIAS shows that CMFD overestimates at light intensity while underestimates at high intensity, which is consistent with previous studies (Aryastana et al., 2022; Tang et al., 2021; Tian et al., 2018). And the detection capability of calibrated‐CMFD is also improved especially for the large precipitation magnitude.…”
Section: Discussionsupporting
confidence: 92%
“…From the AUC analysis, it can be determined that IMERG is the best rain product among GSMaP and PERSIANN that can be used especially in Badung Regency. The best performance of the IMERG product in predicting rainfall events preceding landslide occurrences may be attributed to its high temporal resolution, which enables it to more effectively capture regional variations in sub-daily precipitation [17], [35], [36]. The current findings suggest that the IMERG dataset holds a high potential for establishing rainfall thresholds.…”
Section: Threshold Performance Analysismentioning
confidence: 70%
“…In addition, previous researchers also observed that the use of hourly rainfall data has better capabilities compared to daily rainfall data, which causes a decrease in general predictability [25]. However, the assessment of the PERSIANN dataset revealed its inferiority when compared to IMERG and GSMaP in identifying intense rainfall [40].…”
Section: Discussionmentioning
confidence: 95%